Pseudo-Precision? Precise Forecasts and Impression Management in Managerial Earnings Forecasts - Hayward, Mathew L. A.; Fitza, Markus A. (Academy of Management Journal, 2017)
We examine earnings guidance precision as a mechanism of organization impression management (OIM) and, specifically, suggest that strategic leaders use more precise earnings forecasts as an OIM tactic to convey a greater sense of authority and control over organizational performance after material organizational setbacks. Contributing to the OIM literature, we argue that the use of more precise judgment makes use of different psychological mechanisms compared to kinds of OIM that have been previously studied. The results presented here suggest that (a) OIM is an important motivation for more precise earnings forecasts, (b) precision as an OIM tactic is more likely to arise when managers convey impressions of brighter performance prospects, and (c) investors generally respond favorably to the tactic.